2023
DOI: 10.1021/acs.est.3c01823
|View full text |Cite
|
Sign up to set email alerts
|

Soil Emissions of Reactive Nitrogen Accelerate Summertime Surface Ozone Increases in the North China Plain

Wanshan Tan,
Haolin Wang,
Jiayin Su
et al.

Abstract: Summertime surface ozone in China has been increasing since 2013 despite the policy-driven reduction in fuel combustion emissions of nitrogen oxides (NO x ). Here we examine the role of soil reactive nitrogen (N r , including NO x and nitrous acid (HONO)) emissions in the 2013−2019 ozone increase over the North China Plain (NCP), using GEOS-Chem chemical transport model simulations. We update soil NO x emissions and add soil HONO emissions in GEOS-Chem based on observation-constrained parametrization schemes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…HONO plays a pivotal role in atmospheric chemistry as an important precursor of the hydroxyl radical (OH), which fuels atmospheric chemical cycling and drives the formation of secondary pollutants. The dense agricultural activities result in high primary HONO emissions from various sources, including fertilized soils, livestock farming, and biomass burning in China . Furthermore, the increasing frequency of wildfire events under a warming climate intensifies HONO emissions, accelerating oxidative wildfire chemistry and, consequently, O 3 production.…”
Section: Primary Radical Source (Hono)mentioning
confidence: 99%
See 2 more Smart Citations
“…HONO plays a pivotal role in atmospheric chemistry as an important precursor of the hydroxyl radical (OH), which fuels atmospheric chemical cycling and drives the formation of secondary pollutants. The dense agricultural activities result in high primary HONO emissions from various sources, including fertilized soils, livestock farming, and biomass burning in China . Furthermore, the increasing frequency of wildfire events under a warming climate intensifies HONO emissions, accelerating oxidative wildfire chemistry and, consequently, O 3 production.…”
Section: Primary Radical Source (Hono)mentioning
confidence: 99%
“…Collectively, these factors contribute to increased HONO levels and hence increase the atmospheric oxidizing capacity, resulting in severe environmental consequences. For instance, soil-emitted HONO alone was found to enhance MDA8 O 3 by 2.6 ppb in the North China Plain and up to 7 ppb in the Sichuan Basin in June and July 2019 . Accordingly, HONO mitigation may provide a new O 3 control strategy beyond traditional VOCs or NO x control in China.…”
Section: Primary Radical Source (Hono)mentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies simultaneously considered the impact of soil HONO emissions (denoted as SHONO) along with SNOx on O3 and other secondary pollutants (Tan et al, 2023;Wang et al, 2023b). Wang et al (2023b) found that the NOx and HONO emissions from natural soils (i.e., soil background emissions) increased daily average O3 concentrations by 2.0% in Northeast Plain during August 2016 without considering the contribution from fertilized croplands.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2023b) found that the NOx and HONO emissions from natural soils (i.e., soil background emissions) increased daily average O3 concentrations by 2.0% in Northeast Plain during August 2016 without considering the contribution from fertilized croplands. Tan et al (2023) believed that the contribution of soil NOx and HONO to O3 pollution has been in an increasing trend from 2013 (5.0 pptv) to 2019 (8.0 pptv) in the summer season over the North China Plain by using the GEOS-Chem model; however the coarse resolution of GEOS-Chem simulation may not insufficient to resolve the spatial heterogeneity in soil emission distribution (Lu et al, 2021). Associated with the decreasing anthropogenic emissions is the increasing contribution of soil emissions to the atmospheric nitrogen budget in China.…”
Section: Introductionmentioning
confidence: 99%